Divide the first equation by the second one:
that is
gives
Hence
So
Integrate this.
=
=
For the integrand , substitute
=
=
=
=
=
Substitute back to get the final result.
ok so i was working this problem and got stuck, im not sure what to do with the imaginary numbers that im getting?
so here is the problem...
i figured out that ...
but im not sure where to go from here?
any help would be greatly appreciated
thanks Danny! I was looking through another textbook and saw that similiar form that you gave... the author of the text was saying something to the effect of im going to read through it again and redo this problem, it doesnt seem bad after reading through the explanations posted! This forum is the reason why im passing Diffy Q!